1996
DOI: 10.1007/bf03011254
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of doxacurium during cardiac surgery with hypothermic cardio-pulmonary bypass

Abstract: In contrast with findings in patients without cardiac disease, this study shows comparable onset times of doxacurium with doses of two and three times ED95. The clinical duration of doxacurium is 60 to 100% longer than previously reported in noncardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Vecuronium pharmacokinetics and pharmacodynamics during hypothermic cardiopulmonary bypass in infants and children TUDIES performed both in animals and humans during hypothermic CPB have indicated that hypothermia below 32°C increases sensitivity to vecuronium, 1-5 pancuronium 1,4,6 atracurium, 5,7-9 rocuronium, 10-12 metocurine 13 and doxacurium 14 but not to alcuronium 15,16 or d-tubocurarine. 1,17 Some studies have examined pharmacodynamic parameters only 1,4,5,7,18 but other authors have performed a complete pharmacokinetic-pharmacodynamic study.…”
Section: Methodsmentioning
confidence: 99%
“…Vecuronium pharmacokinetics and pharmacodynamics during hypothermic cardiopulmonary bypass in infants and children TUDIES performed both in animals and humans during hypothermic CPB have indicated that hypothermia below 32°C increases sensitivity to vecuronium, 1-5 pancuronium 1,4,6 atracurium, 5,7-9 rocuronium, 10-12 metocurine 13 and doxacurium 14 but not to alcuronium 15,16 or d-tubocurarine. 1,17 Some studies have examined pharmacodynamic parameters only 1,4,5,7,18 but other authors have performed a complete pharmacokinetic-pharmacodynamic study.…”
Section: Methodsmentioning
confidence: 99%